Modified boundary integral method for pressure driven MHD duct flow - B. D. Aggarwala; P. D. Ariel (International Journal of Mathematics and Mathematical Sciences)
In this paper, we investigate the flow of a viscous, Incompressible, electrically conducting fluid through a rectangular duct in the presence of a magnetic field, when one of the boundaries perpedicular to the magnetic field is partly conducting and partly Insulating, by a modified Boundary Integral Method.